THE INFLUENCE OF BRAND IMAGE, BRAND TRUST, AND CUSTOMER PERCEIVED VALUE IN CREATING CUSTOMER LOYALTY IN HALAL CERTIFICATE OF MUI ON COSMETIC PRODUCT: An Empirical Study on Customer of Wardah Cosmetics in Malang - Absharina, Rastra Atika; Irawanto, Dodi Wirawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
The purpose of this research is to examine the influence of Brand Image, Brand Trust, and Customer Perceived Value in creating Customer Loyalty in Halal Certificate of MUI on Cosmetic Product. The use of these variables enables the writer to observe customers of Wardah Cosmetics in Malang. In order to know the relationship among variables, a regression analysis, F-test, and t-test were applied. The samples in this research are the Muslim customers of Wardah Cosmetics in Malang who purchase the product twice and more. The sampling technique used was a purposive sampling involving 122 respondents. Brand Image, Brand Trust, Customer Perceived Value, and Customer Loyalty were tested using validity test, reliability test, and classical assumption test. The hypothesis testing used F-test and t-test to analyze the data used in Multiple Linear Regression Analysis. The multiple regression analysis result shows that Brand Image, Brand Trust, and Customer Perceived Value have significant effect simultaneously and partially toward Customer Loyalty. The dominant test shows that Brand Image is the most dominant variable influencing the Customer Loyalty. The result of this research can be applied in Marketing Strategy. The company should retain the image, trust, and value of product with halal image in order to always have a positive image on the customers’ eyes which later can influence their loyalty. Keywords: Brand Image, Brand Trust, Customer Loyalty, Customer Perceived Value, Halal Certificate of MUI